The androcentric bias of economic science and the feminist critiques of homo economicus - Grecco, Fabiana Sanches (2018)
A fundamental critique of feminist economists in relation to Economic Science is that this science would be founded on an androcentric bias that would privilege market relations and reasoning in terms of selfish individualities. In this text, this is verified through the analysis of the notion homo economicus in different economic approaches and historical moments. Feminist critiques of this notion are presented, illustrated by Thomas Hobbes’s “mushroom man” idea and Daniel Defoe's character Robinson Crusoe. Opposing this bias, the feminist perspective of economics is presented. It is argued that the analytical and methodological tools of economic science are reinvented by considering extra-market values such as emotions, solidarity, reciprocity.